A Differential Response to Antihypertensive Therapy in African Men and Women: Insights From the CREOLE Trial. (4th February 2022) - Ojji, Dike B; Shedul, Gabriel L; Sani, Mahmoud; Ogah, Okechukwu S; Dzudie, Anastase; Barasa, Felix; Mondo, Charles; Ingabire, Prossie M; Jones, Erika S W; Rayner, Brian; Albertino, Damasceno; Ogola, Elijah; et al.
Abstract: Background: We sought to address the paucity of data to support the evidence-based management of hypertension to achieve optimal blood pressure (BP) control on a sex-specific basis in Africa. Methods: We undertook a post hoc analysis of the multicenter, randomized CREOLE (Comparison of Three Combination Therapies in Lowering Blood Pressure in Black Africans) Trial to test the hypothesis that there would be clinically important differences in office BP control between African men and women. We compared the BP levels of 397 and 238 hypertensive women (63%, 50.9 ± 10.5 years) and men (51.2 ± 11.3 years) from 10 sites across sub-Saharan Africa who completed baseline and 6-month profiling according to their randomly allocated antihypertensive treatment. Results: Overall, 442/635 (69.6%) participants achieved an office BP target of <140/90 mm Hg at 6 months; comprising more women (286/72.0%) than men (156/65.5%) (adjusted odds ratio [OR] 1.59, 95% confidence interval [CI] 1.07–2.39; P = 0.023). Women randomized to amlodipine–hydrochlorothiazide (HCTZ) (adjusted OR 3.03, 95% CI 1.71–5.35; P < 0.001) or amlodipine–perindopril (adjusted OR 2.62, 95% CI 1.49–4.58; P = 0.01) were more likely to achieve this target compared with perindopril–HCTZ. Among men, there were no equivalent treatment differences—amlodipine–HCTZ (OR 1.54, 95% CI 0.76–3.12; P = 0.23) or amlodipine–perindopril (OR 1.32, 95% CI 0.65–2.67; P = 0.44) vs. perindopril–HCTZ. Among the 613 participants (97%) with 24-hour ambulatory BP monitoring, women had significantly lower systolic (124.1 ± 18.1 vs. 127.3 ± 16.9; P = 0.028) and diastolic (72.7 ± 10.4 vs. 75.1 ± 10.5; P = 0.007) BP levels at 6 months compared with men. Conclusions: These data suggest clinically important differences in the therapeutic response to antihypertensive combination therapy among African women compared with African men. Graphical Abstract: